Handmade Paper for Drawing and Painting: A Study on The Use of Mengkirai Fibres to Produce Fine Art Papers - Elham Shafaei, Izmer Ahmad; Adnan Mat (Wacana Seni Journal of Arts Discourse, 2013)
Papermaking has been an important craft of Southeast Asia for seven hundred years. Malaysia's rainforests offer the mengkirai tree as an unexplored material for papermaking. Papers made from the bast fibres of the mengkirai bark have enough tensile strength, elasticity and flexibility for making hand-made fine art papers for drawing and painting. These papers are ideal for a wide range of art media including pencil, charcoal, acrylic and ink. Moreover, their surfaces provide tonal variations with different drawing and painting techniques. This study shows that art papers manufactured from the mengkirai are durable products for Malaysian artists and art students.